Genetic polymorphism analysis of CYP2C19 in Chinese Han populations from different geographic areas of mainland China. (June 2008) - Chen, Lingling; Qin, Shengying; Xie, Jing; Tang, Jimin; Yang, Lun; Shen, Wen; Zhao, Xinzhi; Du, Jing; He, Guang; Feng, Guoyin; He, Lin; Xing, Qinghe
Aims: Although many studies have been performed on CYP2C19, most of them have mainly examined the effects of the defective alleles CYP2C19 * 2 and CYP2C19 * 3 . A comprehensive search for genetic polymorphisms of the CYP2C19 gene in the Chinese Han population has rarely been conducted. The present study was designed to determine the genetic basis of CYP2C19 polymorphisms.Materials & Methods: We investigated the 5´´-regulatory region, all the exons and their surrounding introns of the CYP2C19 gene in 400 unrelated healthy Chinese Han volunteers from four different geographical locations, namely Shanghai, Shantou, Shenyang and Xi''an, with a sample of 100 subjects in each population, using direct sequencing.Results: A total of 14 different CYP2C19 polymorphisms, including one novel variant (-2306G>A) in the enhancer region and a novel nonsynonymous one (905C>G, T302R) were identified. In addition, CYP2C19 * 1, * 2, * 3, * 15 and * 17 alleles showed frequencies of 69.7%, 24.7%, 3.3%, 1.2% and 1.2%, respectively, and CYP2C19 * 15 was the first detected in an Asian population. The frequencies of the prevalent defective alleles CYP2C19 * 2 and CYP2C19 * 3 in Chinese Han populations are similar to those in other Asians, and much higher than those reported in American European and other Caucasian populations. Haplotype analysis demonstrated CATCGG was the dominating haplotype with a frequency of 38.6% in the Chinese Han population. Furthermore, homology modeling analysis for CYP2C19 indicates that Thr302Arg could cause the displacement of heme.Conclusion: This is the first study that systematically screened the polymorphisms of the whole CYP2C19 gene in a large Chinese Han population. The results suggest that a few low frequent variants show significant differences among the four populations, while the prevalent polymorphisms show no differences. Therefore, our database provides important information on CYP2C19 polymorphisms in the Chinese population, and could be helpful for future personalized medicine studies in Asian populations generally.